The effect of tranilast on fibroblast activation protein α (FAP-α) expression in normal and keloid fibroblasts in vitro - Paweł P. Antończak; Magdalena Jurzak; Katarzyna Adamczyk; Agnieszka Garncarczyk; Magdalena Hartman-Petrycka (Termedia Publishing House, 2017)
Introduction . Tranilast (N-(3',4'-demethoxycinnamoyl)-anthranilic acid) is an anti-allergic drug. Its mechanism of action is based on the inhibition of antigen-induced release of chemical mediators from mast cells and basophils. It also reveals antifibroproliferative activities. These properties of tranilast are used in the treatment of hypertrophic scars and keloids. Keloids are characterized by incorrect extracellular matrix components turnover. Fibroblasts derived from keloids reveal overproduction of collagen type I and decreased degradation of extracellular matrix in comparison with normal fibroblasts. Fibroblast activation protein α (FAP-α) may play an important role in remodeling of extracellular matrix and the invasive properties of keloids. Objective . In the present study, the effect of tranilast on expression of FAP-α gene and its protein was evaluated in normal human dermal fibroblasts and fibroblasts derived from keloids cultured in vitro . Materials and methods. In the first stage of the study, the influence of tranilast on cell viability was estimated. The second stage of the study included the quantitative evaluation of FAP-α mRNA expression in normal and keloid fibroblasts treated with tranilast. The third stage of the study comprised fibroblast activation protein α expression analysis in the examined cells treated with tranilast. Results and conclusions . The expression of FAP-α gene and fibroblast activation protein α is higher in keloid fibroblasts. Tranilast at concentrations of 3 μM and 30 μM up-regulated mRNA FAP-α expression in normal fibroblasts but did not influence keloid fibroblasts. The drug, at concentrations of 30 μM and 300 μM up-regulated fibroblast activation protein α expression in normal fibroblasts and did not influence keloid fibroblasts. Tranilast antiproliferative effect is not associated with FAP-α expression in keloid fibroblasts.